High‐dose post‐transplant cyclophosphamide impairs γδ T‐cell reconstitution after haploidentical haematopoietic stem cell transplantation using low‐dose antithymocyte globulin and peripheral blood stem cell graft. Issue 9 (23rd September 2020) - Stocker, Nicolas; Gaugler, Béatrice; Labopin, Myriam; Farge, Agathe; Ye, Yishan; Ricard, Laure; Brissot, Eolia; Duléry, Remy; Sestili, Simona; Battipaglia, Giorgia; Médiavilla, Clémence; Paviglianiti, Annalisa; et al.
Abstract: Objectives: Haploidentical haematopoietic cell transplantation (Haplo‐HCT) using peripheral blood stem cell (PBSC) grafts and post‐transplant cyclophosphamide (PTCy) is being increasingly used; however, data on immunological reconstitution (IR) are still scarce. Methods: This retrospective study evaluated T‐cell immunological reconstitution in 106 adult patients who underwent allogeneic haematopoietic cell transplantation for haematologic malignancies between 2013 and 2016. Results: At D30, while conventional T cells reached similar median counts in Haplo‐HCT recipients ( n  = 19) and controls ( n  = 87), γδ and Vδ2 + T‐cell median counts were significantly lower in Haplo‐HCT recipients and it persists at least until D360 for Vδ2 + T cells. PTCy induces a significant reduction in early γδ and Vδ2 + T‐cell proliferation at D  7. At one year, the rate of increase in Epstein–Barr virus (EBV) viral load was significantly higher in Haplo‐HCT recipients as compared to controls (61% versus 34%, P  = 0.02). In multivariate analysis, a higher γδ T‐cell count (> 4.63 μL −1 ) at D30 was the only independent parameter significantly associated with a reduced risk of increase in EBV viral load (RR 0.34; 95% CI, 0.15–0.76, P  = 0.009). Conclusion: Immunological reconstitution of γδ T cells is significantly delayed after Haplo‐HCT using PTCy and low‐dose ATG and is associated with an increased risk of increase in EBV viral load. Abstract : In this study, immune reconstitution analyses with flow cytometry observed an impaired γ/δ and Vδ2 + T‐cell reconstitution following haploidentical haematopoietic cell transplantation using peripheral blood stem cell grafts and post‐transplant cyclophosphamide (PTCy). PTCy induces a significant reduction in early proliferation of γ/δ and Vδ2 + T‐cell subsets while impaired γ/δ T‐cell recovery was associated with an increased risk of increase in Epstein–Barr virus load.